Prevalence of thyroid disorders in first trimester of pregnancy - Rani, Uzma; Paladi, Rajshree; Anjum, Mehvish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: More recently there has been growing concern that more marginal degrees of thyroid dysfunction particularly subclinical hypothyroidism (elevated TSH and normal T4 concentration) and isolated hypothyroxinemia (normal TSH and low T4) are associated with fetal loss, prematurity and impaired offspring cognitive function and potential risk for fetal loss. Thus, it would seem logical to systematically screen pregnant woman for thyroid disorders. This study focuses specifically on thyroid screening in first trimester of pregnancy. Methods: This is a prospective cross-sectional study over 18 months (December 2020 to June 2022) in 300 patients attending the department of obstetrics and gynecology of teaching hospital attached to Khaja Bandanawaz Institute of Medical Sciences (KBNIMS), KBN University, Gulbarga for antenatal check-up during first trimester of pregnancy. Results: As per our study prevalence of thyroid disorder 14%, subclinical hyperthyroidism 3.67% and subclinical hypothyroidism 10.33%. Conclusions: According to data of our study, it is very ideal to subject all pregnant women for thyroid screening in first trimester with special emphasis to pregnant women in extremes of age, extremes of BMI, bad obstetric history and adverse outcome in previous pregnancy as it shows significant relationship with risk of having thyroid abnormalities.